2016
DOI: 10.1186/s13019-016-0433-z
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle strength is not decreased in patients undergoing cardiac surgery

Abstract: BackgroundPostoperative pulmonary impairments are significant complications after cardiac surgery. Decreased respiratory muscle strength could be one reason for impaired lung function in the postoperative period. The primary aim of this study was to describe respiratory muscle strength before and two months after cardiac surgery. A secondary aim was to describe possible associations between respiratory muscle strength and lung function.MethodsIn this prospective observational study 36 adult cardiac surgery pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
4
19
0
3
Order By: Relevance
“…The results of this study coincided with the results achieved by Charlotte et al, [17] who concluded that respiratory muscle strength was not impaired, either before or two months after cardiac surgery. The reason for post-operative lung function alteration is not yet known.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study coincided with the results achieved by Charlotte et al, [17] who concluded that respiratory muscle strength was not impaired, either before or two months after cardiac surgery. The reason for post-operative lung function alteration is not yet known.…”
Section: Discussionsupporting
confidence: 91%
“…Corroborating in part the results of the current study, Roncada et al (23) concluded that after coronary artery bypass grafting surgery, there was a major reduction in pulmonary function, which the author attributed to changes in circulatory factors that affect the synthesis of muscle proteins. In contrast, Urell et al (9) observed that RMS was not reduced at two months after cardiac surgery. However, the authors did not evaluate patients in the immediate postoperative period; this may be particularly relevant because pain would have needed to be considered.…”
Section: Discussionmentioning
confidence: 88%
“…Corroborating our study, Urell et al showed that RMS was not impaired, neither before nor two months after cardiac surgery. (9)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the relation between respiratory muscle strength and lung function, it should be noted that the study of Urell C. et al determined that respiratory muscle strength is restored and does not reduce two months after CS, unlike lung function. Therefore, the researchers emphasize that interventions aimed at restoring optimal postoperative lung function should focus on other interventions rather than respiratory muscle strength training (Urell et al, 2016).…”
Section: Discussionmentioning
confidence: 99%